A finite element study of welded aluminum shoe-base light pole details. (1st November 2019) - Daneshkhah, Ali Reza; Menzemer, Craig C.
Highlights: The largest hot-spot stresses were observed in the weld toe area. Fatigue cracks developed during tests along the fillet weld toe joining the tube to shoe-base casting. Hot-spot stresses area shows a sensitive region under fatigue loading. The safety factor adjacent to the weld toe (red color) is critical. As expected, the model demonstrates the highest risk of failure in the weld toe region. The safety factor decreases as the stress range increases. Abstract: Cantilevered light poles are examples of lightly damped, slender structural systems subjected to wind (cyclic) loads making fatigue life analysis necessary. Experimental and numerical studies performed on welded aluminum shoe-base details often found on cantilevered light poles included thirty-five fatigue tested in the Structures Laboratory of the University of Akron that provided the basis for the analytical study described in this article. Twenty-two of the thirty-five specimens failed and the remainder taken as run-outs. In an attempt to understand the fatigue behavior of the welded aluminum details, parametric studies using ANSYS examined bolt circle diameter, fillet weld leg-size, socket depth, and tube thickness. An increase in the bolt circle diameter of 27% results in about a 50% increase in the local stress adjacent to the fillet weld, and a reduction in tip deflection. A 50% increase in the fillet weld leg-size from 6.35 mm (0.25 in.) to 9.5 mm (0.375 in.) corresponds to about a 14% increase in the local stress. Increasing the shoe-base socket depth by 51% leads to an increase of 36% in the local stress. An increase in the thickness of 40% from 6.35 mm (0.25 in.) to 8.9 mm (0.35 in.) reflects a 60% increase in local stress. The analysis demonstrated that the lowest factor of safety was observed adjacent to the toe of the fillet weld. Thermographic measurements confirmed the existence of a hot spot near the weld toe on the tube.